Efeito da ressinterização sobre a resistência à flexão da zircônia Y-TZP em função do desgaste - Hatanaka, Gabriel Rodrigues [UNESP] (2015)
The aim of this study was to evaluate the resintering effect on the flexural strength of zirconia partially stabilized by yttria of Lava™ system after wet and dry grinding. Bar shaped specimens were distributed into 6 groups (n=16) according to grinding (G), water coolant (W) and resintering (R) to compose the following groups: G-R- (control), GR+, G+W-R-, G+W-R+, G+W+R-, G+W+R+. Grinding (0.3 mm) were conducted in a standardize grinding device using high-speed handpiece and 150 µm diamond bur with or without water coolant. Resintering was conducted at 1000°C for 30 minutes. Four-point bending test was made in MTS 810 (10 KN, 0.5 mm/min). It was used scanning electron microscope (SEM) for analysis of surface topography and X-ray diffractometer for the identification of phases. Data were analyzed by Kruskal-Wallis analysis of variance and Dunn's test (α=.05). Flexural strength was statistically higher for ground groups (G+) than for non-ground groups (G-), regardless of water coolant. SEM showed no difference in surface topography between ground groups and XRD analysis showed that for G+ groups the presence of monoclinic phase disappeared after resintering. It was concluded that grinding, regardless of water coolant, increased the flexural strength of Y-TZP zirconia and induced the tetragonal-monoclinic transformation, resintering did not change the strength and no monoclinic phase was found after heat treatment.